THE ROLE OF MEDIA IN SHAPING POLITICAL DISCOURSE IN THE CONTEXT OF THE RUSSIAN-UKRAINIAN WAR - Chekshturina, Victoria (Public Management and Policy, 2024)
The article examines the role of the media in shaping political discourse during the Russian-Ukrainian war. The main focus is on how the media influence the perception of events, mobilize public opinion and spread narratives in different social groups. The concepts of political discourse, conflict, narratives, and propaganda are defined. The purpose of the study is to analyze the narratives used by Russian and Ukrainian media, to determine how Russian propaganda manipulates the audience by distorting facts, and how Ukraine counteracts this through information campaigns in the media and social networks. The sources for the study of the role of media in shaping political discourse in the context of the Russian-Ukrainian war are academic papers and research articles, analytical reports and studies by media monitoring organizations, and media content. To achieve this goal, a number of general scientific research methods were used: the historical method allowed us to identify the transformation of the role of the media in international conflicts. The systematic method helped to identify general trends in the impact of the media on international conflicts. The author analyzes the media as an instrument of information warfare, studying their ability to shape national identity, political positions, and support Ukraine’s international image. The study focuses on manipulative technologies, disinformation and propaganda used in the media space. Particular attention is paid to the role of disinformation, propaganda and information attacks used to manipulate public opinion and undermine trust in Ukrainian and international information sources. The study found that the media play a central role in shaping political discourse during the Russian-Ukrainian war. It is determined that the media actively influence the formation of public perception of the events of the war, supporting national narratives and strengthening Ukrainian identity. The analysis shows that Ukrainian and international media play an important role in countering Russian propaganda and disinformation. The article proves that effective counter-narratives help to neutralize manipulative messages spread through pro-Russian media and social platforms. It is proved that through the coverage of the conflict, the media influence the international community, contributing to diplomatic and military support for Ukraine. The scientific novelty is that the media is not just a source of information, but also an active participant in political and military processes, determining the development of the war discourse at both the national and international levels.